(untitled) (Sains Humanika, 2014)
This study is to find out information channelsÂ used by final year student for academic purposes, selection factors and problems in using these channels by final year student of higher learning institution. 102 students teacher were selected as respondents. Questionnaire with Alpha Cronbach 0.949 was used as the instrument for this survey. The channels studied were the Internet, Wikipedia, blog, electrronic communications, library, lecturer, expert, friend, electronic database, printed materials and social networking. This study shows that the Internet is the most popular choice because of fast and easy access. Social networking are the least popular because of low quality and too much not related information. But traditional channels such as library and electronic database is still among the prefered choice by students bacause ofÂ information quality and credibility.